Evaluation of the Periodic Road Maintenance Work Package: Talaga – Bts. Majalengka/Sumedang (Krisik) Road Section - Aep Rochman; Anton Susanto; Agus Topan (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
The Talaga – Bts Majalengka/Sumedang (Krisik) road section is a critical infrastructure link in West Java, Indonesia, requiring periodic maintenance to ensure structural integrity and serviceability. This study aims to evaluate the implementation of the major pavement layers—specifically the Asphalt Concrete Wearing Course (AC-WC) and Asphalt Concrete Binder Course (AC-BC)—within a periodic maintenance work package against the technical specifications of Bina Marga 2018 Revision 2. Field data, including aggregate gradation, asphalt properties, Marshall mix parameters, and construction practices, were collected and analyzed descriptively. The results show that all material properties and field execution parameters—such as gradation, asphalt penetration, Marshall stability, voids in mix, compaction stages, and paving temperature—fully comply with the required standards. The research confirms that the quality of the AC-WC and AC-BC layers meets the specifications, thereby ensuring the pavement’s performance and durability. Recommendations include stricter control of post-compaction finishing and continuous evaluation of all Bill of Quantity (BOQ) items to enhance long-term road maintenance outcomes.